NOx emission reduction from gas burner system applying water cooling technique - Mohd. Jaafar, Mohammad Nazri; Andrews, G. E.; MkPadi, M. C. (Faculty of Mechanical Engineering, 2000)
A gas burner system applying water cooling heat exchanger has been investigated using a 140 mm inside diameter combustor of 294 mm length. The combustor was placed vertically upwards All tests were coducted using natural gas only. A fixed straight blade radial swirler with 76 mm outlet diameter was placed at the inlet plane of the combustor. An orifice plate of 59 mm was inserted at the exist plane of the swirler to enhance turbulence and help in mixing of the fuel and air. Fuel was injected at the back plate of the swirler using central fuel injector with eight fuel holes ponted radially outward. Tests were conducted at 2 mmW.G. pressure loss. A reduction of about 20 per cent on NOx emissions was achieved at equivalence ratio of near stoichiometric (0.9). Other emissions such as carbon monoxide were well under 100 ppm except below equivalence ratio of near 0.5 due to cooling effect. Unburned hydrocarbon emissions were well below 10 ppm except below equivalence ratio of 0.5.